Gender and Same-Sex Intimate Partner Violence: A Systematic Literature Review - Correia De Barros, Isa (2019)
The infl uence of gender on intimate partner violence (IPV) has been predominantly studied in opposite sex relationships. This article presents the results of a systematic literature review in which the aim was to understand how gender may aff ect not only the violence in same-sex IPV but also, and mostly, each element of the couple and third-party responses. The search was conducted in four electronic databases: B-on, PubMed, Sage and PsycINFO. From the analysis of seven articles selected, four major domains were identifi ed in which gender aff ects these relationships: normalizing violence; diffi culty in recognizing violence; diffi culty in seeking help; and social isolation. It was concluded that gender, or gender role expectations, cannot be ignored while studying this phenomenon. More than infl uencing violence per se, gender shapes the way each element of the couple perceives their experiences and third-party perceptions (e.g., family, friends, justice system, and victims support services professionals), preventing an adequate social response to this form of violence.